Spray drying of nanoparticles to form fast dissolving glipizide (Asian Journal of Pharmaceutics (AJP), 2015)
Poor water solubility of pharmaceutical candidates creates a big barrier to development and clinical applications. In thisstudy, glipizide as a poorly water soluble drug was precipitated as nanoparticles and processed by spray drying to producefast dissolving powders. Nanosuspensions of glipizide were prepared using the sonoprecipitation technique in the presence ofselected stabilizers. Sorbitol, mannitol, and microcrystalline cellulose (Avicel) were involved in the formulations as the carrierof drug nanoparticles for spray drying process. Physicochemical characteristics of nano and microparticles were determined aswell as maximum saturation solubility and dissolution profile of processed powders.The screening data introduced the sodiumlauryl sulfate as the better nanosuspension stabilizer. Particle size and yield of nanosuspension formulations were in the rangeof 262.2–498.8 nm and 65.50–95.21%, respectively. The particle sizes of spray dried powders were between 2.27 μm and29.25 μm and dissolution of the drug from these micropaticles 58.45–81.65% during the first 5 min. Spray drying of glipizidenanosuspension would be a promising approach to enhance drug solubility as well as physicochemical properties.Key words: Avicel, glipizide, nanosuspension, spray drying, sugar carrier